Anal tuberculosis presented as chronic perianal abscess in an immunocompetent adult: A rare case report - Pratyaksha Kumari; Ananda Datta; Archana Malik; Lee Chang M. Sangma; Sumeet Sawale; Abhinav Prakash Arya; Sarthak Das (Journal of Family Medicine and Primary Care, 2024)
There are reported 7.5 million cases of extra pulmonary tuberculosis (TB) (EPTB) worldwide and 19% in the South-East Asia region. Anal TB represents an exceedingly uncommon extra pulmonary manifestation of TB), occurring in fewer than 1% of individuals who acquire TB. The occurrence of perianal illness is extremely rare, accounting for 1% of the gastrointestinal (GI) tract, while GI TB makes up less than 1% of all TB cases. The most prevalent manifestation is the development of a fistula in the anus, while the presentation as a perianal abscess is uncommon. We present a case of isolated perianal TB with no associated GI or pulmonary dissemination in the immunocompetent.